1996
DOI: 10.1046/j.1365-2125.1996.03601.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzyme inducing anticonvulsants on ethosuximide pharmacokinetics in epileptic patients

Abstract: 1To assess the effect of enzyme inducing anticonvulsants on ethosuximide pharmacokinetics, plasma ethosuximide concentrations after a single oral dose (500 mg) of the drug were compared in 12 healthy control subjects and 10 epileptic patients receiving chronic therapy with phenobarbitone, phenytoin and/or carbamazepine. 2Compared with controls, epileptic patients showed markedly shorter ethosuximide half‐lives (29.0±7.8 vs 53.7±14.3 h, means±s.d., P<0.001) and higher apparent oral clearance (CL/F) values (15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…According to the study protocol, 12 subjects had to complete both treatments, a sample size that in previous studies with similar design was adequate in demonstrating induction of metabolism of low‐clearance substrates (14–18). The study was approved by the Ethics Committee of the University of Pavia.…”
Section: Methodsmentioning
confidence: 99%
“…According to the study protocol, 12 subjects had to complete both treatments, a sample size that in previous studies with similar design was adequate in demonstrating induction of metabolism of low‐clearance substrates (14–18). The study was approved by the Ethics Committee of the University of Pavia.…”
Section: Methodsmentioning
confidence: 99%
“…The clearance of ethosuximide is increased in epileptic patients who are co-medicated with enzyme-inducing anticonvulsant drugs, resulting in lower plasma levels of ethosuximide. Giaccone et al (1996) have shown that the rate of ethosuximide metabolism in patients receiving phenobarbital, phenytoin, or carbamazepine is higher than that in control subjects. In order to evaluate the combination of ethosuximide and valproate experimentally, this combination has been studied in mice to define their pharmacodynamic interactions and the efficacy-toxicity ratio.…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…Enzyme‐inducing AEDs and rifampicin enhance the metabolism of ethosuximide, resulting in lower serum concentrations (Giaccone et al, 1996; Riva et al, 1996; Tanaka, 1999). In contrast, serum ethosuximide concentrations are increased by isoniazid (van Wieringen & Vrijlandt, 1983).…”
Section: Relevance Of Tdm For Individual Aedsmentioning
confidence: 99%